Alanine Scan of an Immunosuppressive Peptide (CP): Analysis of Structure–Function Relationships. (26th November 2012) - Raguine, Laura; Ali, Marina; Bender, Veronika; Diefenbach, Eve; Doddareddy, Munikumar Reddy; Hibbs, David; Manolios, Nicholas
<x xml:space="preserve">Abstract</x> Core peptide is a hydrophobic peptide, the sequence of which is derived from the T‐cell antigen receptor alpha‐chain transmembrane region. Previous studies have shown that core peptide can inhibit T‐cell‐mediated immune responses both in vitro and in vivo. Here, we report the role each constituent amino acid plays within core peptide using an alanine scan and the amino acid effect on function using a biological antigen presentation assay. The biophysical behaviour of these analogues in model membranes was analysed using surface plasmon resonance studies and then binding correlated with T‐cell function. Removal of any single hydrophobic amino acid between the two charged amino acids in core peptide (R, K) resulted in lower binding. Changing the overall net charge of core peptide, by removing either of the positively charged residues (R or K), had varying effects on peptide binding and IL‐2 production. There was a direct correlation (ρ = 0.718) between peptide binding to model membranes and peptide ability to inhibit IL‐2. Except for IL‐2 inhibition, production of other T‐cell cytokines such as GM‐CSF, IFN‐γ, IL‐1α, IL‐4, IL‐5, IL‐6, IL‐10, IL‐17 and T‐cell antigen receptor alpha‐chain was not detected using a fluorescent bead immunoassay. This study provides important structure–function relationships essential for further drug design.